Investigating the Role of BAFF and Its Receptors in Renal Transplant Recipients with Chronic Antibody-Mediated Rejection - Shima Afzali; Saeedeh Salehi; Abbas Shahi; Marzie Esmaeili; Samad Farashi Bonab; Azin Peykari; Farzaneh Bagherpour; Bita Ansaripour; Tayebeh Soleimanian; Fatemeh Pour-Reza-Gholi; Aliakbar Amirzargar (Journal of Immunology Research)
Background. Kidney transplantation is the best treatment option for end stage renal disease (ESRD), but graft rejection is still a big obstacle that occurs in spite of immunosuppressive therapy. B cells are considered as the major reason for renal graft rejection because of antibody production. Due to their roles in B cell function, we intended to evaluate the B cell activating factor (BAFF) and its receptors including BAFF receptor (BAFF-R), B cell maturation antigen (BCMA), and transmembrane activator and cyclophilin ligand interactor (TACI) in renal transplant patients. Method. The study included 40 kidney allograft patients with cAMR, 40 stable kidney allograft patients, and 8 healthy volunteers with normal kidney function. The percentage and absolute number of CD19+ B cells were analyzed by flow cytometry, the serum level of BAFF was analyzed by ELISA, and mRNA expressions of BAFF and BAFF receptors (BAFF-R, BCMA, and TACI) were measured using quantitative real-time PCR. Results. The percentage and the absolute number of B cells decreased significantly in stable and cAMR patients compared to healthy individuals. The serum level and gene expression of BAFF, as well as the mRNA level of BCMA, were increased significantly in both cAMR and stable patients compared to healthy volunteers. There was an overexpression of TACI mRNA in cAMR patients compared to stable patients. Conclusions. Both soluble protein and mRNA transcript of BAFF increased in transplant recipients. However, BAFF neither at the serum level nor at the mRNA transcript level cannot be a good biomarker for the prediction of cAMR. In addition, expression of TACI, compared to other receptors of BAFF, confers a potential to be used in distinguishing cAMR and stable kidney transplant patients.